(untitled) (TAJ: Journal of Teachers Association, 2020)
This is a hospital-based cross sectional descriptive study was carried out during January 2015 to June 2015 in the Department of Obstetrics and Gynaecology of Rajshahi Medical College Hospital to determine pregnancy outcome in placenta praevia cases with delayed child bearing age. Total 8107 patients were admitted during the study period and among them 82 patients were diagnosed as placenta praevia. Patients were categorized into two groups as above 35 years & below 35 years and relationship between advanced maternal age and placenta praevia was seen. Socio-demographic condition, clinical condition, course of management, maternal and perinatal outcome were observed and recorded. Proportion of placenta praevia was 1.01% during the study time. Among 82 patients of placenta praevia, 25 were advanced maternal age group (30.49%). Prevalence of placenta praevia in advanced maternal age group in comparison to below 35 years among total admitted patient was seen 9.73% and 0.73% respectively. So, incidence is more in advanced maternal age group which is statistically significant (p<0.05). Most of the patients of placenta praevia came from middle class family 42(51.21%) and most women were multi gravida 75(91.5%). 42.68% patient had history of caesarean section and 47.56% patients had history of menstrual regulation (MR), abortion & dilatation, evacuation & curettage (DE & C). Major placenta praevia was more in advanced maternal age group (64%) which is statistically significant (<0.05) and mode of delivery was caesarean section 62(75.60%). Maternal and perinatal complications were more in advanced maternal age group. Maternal mortality rate 9(10.97%) and perinatal mortality rate 14(17.07%). Advanced maternal age has a relation with placenta praevia and associated with more adverse maternal and perinatal outcome. So, pregnancy in advanced age should be considered as a risk factor for developing placenta praevia. TAJ 2019; 32(2): 48-55